SUBAL lERN MOVE:MENTS AND INDIAN CHURCHES OF INDIGENOUS ORIGINS: . - Hedlund, Roger E. (Journal of Dharma, 1998)
A subaltern approach to Christian studies seeks the viewpoint of the non-elite. In terms of Christian institutions in India, perspectives arising "from below", through local initiative, may be classed as subaltern. They were not imposed. They are the expression of local people, not so privileged, marginalized or oppressed. Whether this approach, in itself, is adequate or sufficient is open to question. Subaltern reconstructions of history tend to "deconstruct" all previous perceptions of history and to assume that they were deficient. In point of fact, indigenous movements of Christianity in India have preceded, coincided, and followed events which occurred during the time of British rule. At the present time large numbers of people, attracted by the values of Christianity, are drawn into indigenous movements. Nor were such movements ever exclusively confined to exploited sections of society.